Metamorphic objects for dynamic reconfiguration of CORBA-based applications. - Elsaesser, Derek Shawn. (University of Ottawa (Canada), 2000)
This thesis presents a solution to the problem of dynamic reconfiguration of distributed applications. This solution is based on the concept of a metamorphic object, which can dynamically change its interface, class definition, and implementation without invalidating existing client object references. The concept of object metamorphism is introduced and discussed. Forwarding is proposed as a mechanism for realizing metamorphic objects in a distributed computing environment and the Forwarder design pattern is presented. A framework for developing distributed applications using metamorphic objects is presented as a specification for a Dynamic Versioning Service for the Common Object Request Broker Architecture. A test application is developed to evaluate the versioning of metamorphic objects and to measure the impact on performance. It is found that the ability to transform an individual object to a new class definition and implementation, without interruption in service, results in only a slight increase in operation invocation time.
Keywords: Engineering, Electronics and Electrical.